Larousse gastronomique recipe collection, Vegetables & salads (London, 2004)
A resource of more than 600 classic vegetable and salad preparations, along with recipes for basics such as sauces, dressings, pastries, butters, stocks, and more. It features vegetable and salad recipes, such as Asparagus Mousse, Gratin Dauphinois, Mushroom Duxelles, and Corn Fritters.
Keywords: Cooking (vegetable); Cuisine (Le?gumes); Salads